ChemInform Abstract: Thermal‐Reductive Transformations of Carbon Dioxide Catalyzed by Small Molecules Using Earth‐Abundant Elements. Issue 49 (December 2015) - Liu, Muhua; Qin, Tian; Zhang, Qingqing; Fang, Chi; Fu, Yao; Lin, Bo‐Lin
Abstract: Review: 50 refs.